Muscle : fundamental biology and mechanisms of disease - Hill, Joseph A.; Olson, Eric N.; Griendling, Kathy K. (Academic Press, 2012)
Muscle: Fundamental Biology and Mechanisms of Disease will be the first reference covering cardiac, skeletal, and smooth muscle in fundamental, basic science, translational biology, disease mechanism, and therapeutics. Currently there are no publications covering the science behind the medicine, as the majority of books are 90% clinical and 10% science. Muscle: Fundamental Biology and Mechanisms of Disease will discuss myocyte biology, also known as muscle cell biology, providing information about the science behind clinical work and therapeutics with a 90% science and 10% clinical focus. A needed resource for researchers, clinical professionals, postdocs, and graduate students, this publication will further discuss basic biology development and physiology, how processes go awry in disease states, and how the defective pathways are targeted for therapy. This book will assist both the new and experienced clinician's and researcher's need for science translation of background research into clinical applications, bridging the gap between research and clinical knowledge.